Competing Taxonomies: Reexamination of the female-based genera of Brachycistidinae (Hymenoptera: Tiphiidae) - Kimsey, Lynn S. (Zootaxa, 2006)
Analysis of the female-based genera of the tiphiid wasp subfamily Brachycistidinae revealed the need to remove Astigmometopa Mickel & Krombein from synonymy with Brachycistis and synonymize it under Glyptacros Mickel & Krombein, synonymize the genus Quemaya Pate under Stilbopogon Mickel & Krombein, synonymize Bruesiella Mann and Aulacros Mickel & Krombein under Brachycistis Fox, and synonymize Xeroglypta Mickel & Krombein under Glyptacros. , In addition, shared characteristics found only in Aglyptacros Mickel & Krombein and Colocistis Krombein demonstrate the need toand synonymize Aglyptacros under Colocistis. Females This is the first time that females have been identified for two genera, Colocistis and Stilbopogon. Previously, females were only known for Brachycistis.[neither of the previous two sentences make sense in light of the rest of the ms – the first suggests either that you are describing two femalebased genera and the second that there has, until now, only been one-please clarify this], Phylogenetic analysis of the generic groupings based upon 21 binary morphological characters resulted in two moderately supported clades, Aglyptacros Colocistis+ Brachycistis, Glyptacros, and Stilbopogon + Genus A (an unnamed, phylogenetically discrete group of females). New generic combinations involve moving all of the species of Quemaya into Stilbopogon; the placement of Bruesiella formicaria Mann, Glyptometopa americana Ashmead, Eurycros furtivus Mickel & Krombein and Aulacros latior Mickel & Krombein in Brachycistis; the assignment of Glyptometopa eureka Banks to Colocistis and Xeroglypta egregia Mickel & Krombein and Astigmometopa emarginata Mickel & Krombein to Glyptacros.